Effect of Clove Powder and Modified Atmosphere Packaging on the Oxidative and Sensory Quality of Chicken Meat Caruncles During Ambient Storage (35±20C) Conditions - Singh, Parminder; Sahoo, Jhari; Chatli , K. Manish; Biswas, Ashim K. (Journal of Meat Science, 2014)
The individual as well as synergistic effect of modified atmosphere packaging and clove powder as natural preservative on the oxidative and sensory quality of chicken meat caruncles during storage at 35±2°C at 70% R.H. for 60 days was evaluated. For this, four different batches of chicken meat caruncles were prepared i.e. CA (control, aerobic packaging), CMAP (Control, 50:50 CO2 /N2 modified atmosphere packaging), TA (treated with 0.2% clove powder, aerobic packaging) and TMAP (treated with 0.2% clove powder, 50:50 CO2/N2 modified atmosphere packaging). In oxidative quality, TBARS value of TMAP sample was significantly lower (P<0.05) than CA sample and was marginally lower than CMAP and TA samples. TA and TMAP samples showed significantly higher (P<0.05) DPPH % inhibition as compared to control counterparts (CA and CMAP). The ABTS % inhibition was significantly higher (P<0.05) in TA (88.26) and TMAP (89.81) as compared to CA (56.93) and CMAP (71.43) samples. Among sensory attributes, colour / appearance was significantly higher (P<0.05) in TA batch than CMAP and TMAP. Flavour score of TA sample was significantly higher (P<0.05) than CA. Crispiness of TMAP was significantly higher (P<0.05) than TA. The scores of all the samples for after-taste, meat flavour intensity and overall acceptability did not vary significantly among themselves. The use of 50%CO2+50%N2 (MAP) in combination with 0.2% clove powder was effective for maintaining the oxidative and sensory quality of chicken meat caruncles at ambient storage conditions.